Promoting independence in Lewy body dementia through exercise (PRIDE) study: Protocol for a pilot study - Michael Inskip (Contemporary Clinical Trials Communications, 2019)
Background: Lewy Body dementia (LBD) is the second most prevalent neurodegenerative dementia. This form of dementia is notable for an aggressive disease course consisting of a combination of cognitive, Parkinsonian, affective, and physiological symptoms that significantly increase morbidity and mortality, and decrease life expectancy in this population compared to more common dementias. Additionally, those diagnosed with LBD are often excluded from trials evaluating exercise in similar diseases such as Alzheimer's disease or Parkinson's disease due to the complexity and concurrency of motor and cognitive symptoms. Consequently, there is scarce research evaluating the effect of exercise on individuals with LBD. Methods: The PRomoting Independence in Lewy Body Dementia through Exercise (PRIDE) trial is a novel non-randomised, crossover pilot study consisting of an 8-week wait-list usual care period, followed by an 8-week exercise intervention targeting progressive resistance and balance training. The trial aim is to evaluate the effect of exercise on the primary outcome of functional independence and secondary outcomes including cognitive, physical, psychosocial and quality of life measures in people living with LBD and their caregivers. The intervention involves 3 supervised 1-h sessions per week (24 sessions in total) administered by an Accredited Exercise Physiologist in a clinical facility at the University of Sydney in Lidcombe, Australia. Discussion: The PRIDE study is the first controlled trial to evaluate a robust exercise intervention within a LBD cohort and will provide crucial information required to inform robust future clinical trials. Trial registration: Australia and New Zealand Trial Register (ANZCTR): ACTRN12616000466448; Key words: Lewy body; dementia; exercise; anabolic; functional independence. Keywords: Lewy body, Dementia, Exercise, Anabolic, Functional independence